AKUNTABILITAS PELAKSANAAN DANA DESA DI DESA NGLURUP KECAMATAN SAMPUNG KABUPATEN PONOROGO TAHUN 2019 - Purwanto, Rudy Aris (JI@P, 2021)
This research is motivated by problems related to the management of village funds. The level of budget absorption and also management which continues to experience positive increases from year to year, but in terms of the accountability report, it has not carried out village financial administration properly. On the basis of these problems, this study aims to analyze and describe the accountability of village fund management in Nglurup Village, Sampung District, Ponorogo Regency in 2019. The accountability theory in this study uses Ellwood in Mardiasmo (2009: 21) that the management of village funds must be based on honesty and accountability. law, process accountability, program accountability and policy accountability. This study uses a descriptive method with a qualitative approach. Research informants using purposive sampling technique. Data collection techniques using in-depth interviews and documentation. The data analysis technique used is interactive analysis consisting of data collection, data condensation, data presentation and conclusion drawing. The results showed that the Nglurup Village Government in managing village funds had shown accountability, both from the dimensions of honesty and legal accountability, process accountability, program accountability and policy accountability.